The impact of defendant gender and attractiveness on juror decision-making in a sexual offense case - Winters, Georgia M. (Deviant behavior, 2022)
In recent years, instances of educator sexual assault against students have flooded the media. In particular, female teachers who abused students have seized the public’s attention as they are often portrayed as attractive and a sexual fantasy. This portrayal can then impact the way society perceives these sexual assaults. Importantly, however, it is not known whether this perception influences the prosecution and sentencing of these cases. The current study examined the impact of gender and attractiveness of a teacher, as well as gender of the student victim, on juror decision-making in a teacher/student sexual assault case. Using a 2 (Teacher Gender) X 2 (Student Gender) X 3 (Attractiveness Level: Attractive/Unattractive/No Photo) experimental design, we examined jurors’ decisions regarding guilt, sentencing, and perceptions of the teacher and student. Results suggest that the gender of the teacher may impact juror decision-making; however, the level of attractiveness of the teacher and gender of the student had minimal effects. The study contributes to our understanding of how educators who commit sexual acts against students are perceived and treated in the court system.